Traditional Indonesian storytelling: a potential multilevel health promotion tool for the poor and a search for a community model - Emma Wherrett (Fakultas Kedokteran Universitas Gadjah Mada, 2019)
In 2018 nearly 10% of Indonesians lived in poverty and a significantly larger number were at risk of falling into poverty. Health promotion efforts which target this population ideally need to be holistic and multilevel so as to address the inequities they experience in health, nutrition, living conditions, education, and employment. This paper explores the potential of traditional Indonesian stories as a health promotion tool and seeks to open discussion into how they can be used in the future. Narratives have the potential to influence people’s beliefs, knowledge, attitudes, values and behaviours. They are increasingly used in health communication due to their ability to overcome resistance in the listener, culturally ground messages and reach less educated audiences. While the use of traditional Indonesian stories in early childhood education is well documented, their potential to address multiple social determinants of disease in a public health context has not been explored. Indonesian stories are a rich source of local wisdom containing important messages about environmental preservation, food wastage and social values such as honesty, justice and peace. They can also be adapted to focus on hygiene, nutrition and encourage preventative health actions. Stories which build resilience and courage might be helpful for the poor, while stories that highlight injustice and discrimination could promote equity in the mindset of the powers that oppress them. There are several limitations however, so an indiscriminate use of traditional stories would be inadvisable. In conclusion it appears that traditional storytelling is currently an underutilised health promotion tool in Indonesia and its potential as a low cost, culturally appropriate and enjoyable way to address determinants of health at multiple levels could be further explored.